2020
DOI: 10.17583/qre.2020.5872
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Distance Education During the (Covid-19) Pandemic Period

Abstract: The purpose of this study is to reveal the perceptions of the teachers, administrators, and academics who had to continue distance education during COVID-19 epidemic disease period, about the problems they experienced and the strategies to cope with the challenges. The working group of the current study consists of 65 teachers. The data were collected via an open-endedwritten interview. Content analysis was applied for analysis of the data gathered. Various important results regarding the use of distance educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
135
0
22

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(169 citation statements)
references
References 22 publications
12
135
0
22
Order By: Relevance
“…Although e-learning has become a topic of discussion in the late 1990s, only now, during the 2020 pandemic, it seems that the world has focused almost entirely on e-learning for a longer or shorter period of time, adapting and re-adapting to the new reality. More and more studies [2][3][4][5][6][7][8][9][10][11] have begun to emerge in this field of research, as it has become increasingly exploratory and fertile for worldwide researchers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although e-learning has become a topic of discussion in the late 1990s, only now, during the 2020 pandemic, it seems that the world has focused almost entirely on e-learning for a longer or shorter period of time, adapting and re-adapting to the new reality. More and more studies [2][3][4][5][6][7][8][9][10][11] have begun to emerge in this field of research, as it has become increasingly exploratory and fertile for worldwide researchers.…”
Section: Introductionmentioning
confidence: 99%
“…With the mass transition to online education, many studies [2][3][4][5][6][7][8][9][10][11] have looked at the concept of e-learning. A large-scale study [2], involving no less than 424 universities around the world affected by the pandemic, shows that for areas and sub-domains, such as research, exchanges of experience between universities, scientific conferences, and, of course, the education process, there is a single solution, namely the adaptation of the whole process to the online environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted in Turkey found obstacles during the COVID-19 plague in the process of online learning, inter alia students' inability to access the internet, weak infrastructure, and lack of ability to use communication and information technology. Another problem is about management in the classroom so that students cannot help but follow the subject matter given during the teaching and learning process properly (Sari & Nayir, 2020).…”
Section: Barriers To the Distance Learning Processmentioning
confidence: 99%
“…Research in Turkey has several solutions to overcome problems during the online learning process, namely improving classroom management by changing the syllabus, preparing new learning activities, motivating students, and using learning courses with different materials. The way to overcome other obstacles is to ask for help from internet providers, colleagues, family, or experts' assistance (Sari & Nayir, 2020).…”
Section: Troubleshooting Solutionsmentioning
confidence: 99%